Family Members Impact on Physical Activity Levels and Enjoyment in Preschool-Aged Children - Bowers, Madison (East Carolina University)
Purpose: The primary purpose of this study was to investigate the impact mothers and older siblings have on the physical activity levels of preschoolers. Secondarily, the preschooler's co-participation enjoyment was explored as well. Methods: A sample of 27 families (mother, sibling, and preschooler) participated in a one-time research visit. During the visit, there were two 20-minute play sessions: preschooler playing with mother and preschooler playing with older sibling independently. During the play sessions the participants were given a variety of sedentary and physical activities to choose from. Total physical activity counts during each play session were measured with an accelerometer. Enjoyment of physical activity co-participation was measured using a smiley face Likert scale. Data were analyzed using a paired t-test to compare total physical activity counts of the preschooler when playing with mother and when playing with older sibling. A paired t-test was also used to compare preschooler's rating of enjoyment of physical activity co-participation between the mother and older sibling. Results: This study found that preschooler's physical activity levels are similar when playing with their mothers (47,071.22 ± 19,653.04 counts per second) and older siblings (54,530.81 ± 20,791.38 counts per second) (p=.21). For enjoyment, there was no significant difference between the preschooler's rating of enjoyment when playing with their mother or older sibling (4.76 ± .52 and 4.88 ± .86, respectively; p=.31). However, a higher percentage of preschoolers said they enjoyed playing with their mother (62%) more than their older sibling (38%) when asked. Discussion: The findings of this study show that both mothers and older siblings have a positive impact on preschoolers' physical activity. This study further expands on the existing literature suggesting that families need to continue to be investigated as a determinate of physical activity for preschoolers. The novel findings on enjoyment of co-participation of physical activity contribute to the small amount of existing literature suggesting that enjoyment of co-participation needs to be further explored as a determinate of preschooler physical activity.
Keywords: Physical Activity; Preschool children--Health and hygiene; Preschool children--Attitudes; Siblings--Family relationships; Mother and child; Play